2011
DOI: 10.2147/opth.s22093
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of retinal circulation measurements obtained using laser speckle flowgraphy-NAVI in patients with glaucoma

Abstract: Background:Laser speckle flowgraphy (LSFG) enables noninvasive quantification of the retinal circulation in glaucoma patients. In this study, we tested the intrasession reproducibility of LSFG-NAVI, a modified LSFG technique.Methods:Sixty-five eyes from 33 subjects (male (M):female (F) = 17:16) with a mean age of 49.4 ± 11.2 years were examined in this study. Two parameters indicating reproducibility – the coefficient of variation (COV) and the intraclass correlation coefficient (ICC) – were analyzed three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 29 publications
5
130
1
Order By: Relevance
“…Beyond bench-side physiological research, there are direct implications for prognostic, diagnostic, and intraoperative imaging applications, as speckle imaging of microcirculatory flows is increasingly becoming applied for gauging local and systemic tissue health [8,9]. Consequently, laser speckle flowmetry studies are expanding in dermatological [10][11][12][13][14], ophthalmological [15][16][17], and neurosurgical settings [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond bench-side physiological research, there are direct implications for prognostic, diagnostic, and intraoperative imaging applications, as speckle imaging of microcirculatory flows is increasingly becoming applied for gauging local and systemic tissue health [8,9]. Consequently, laser speckle flowmetry studies are expanding in dermatological [10][11][12][13][14], ophthalmological [15][16][17], and neurosurgical settings [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…11 However, the mechanism underlying choroidal hyperpermeability remains incompletely understood. Laser speckle flowgraphy (LSFG) can noninvasively measure ocular circulation within 4 seconds, using the laser speckle phenomenon, [12][13][14] with the advantage of providing reproducible 15 data throughout the course of diseases. 13 The mean blur rate (MBR) is a quantitative index of relative blood flow velocity.…”
mentioning
confidence: 99%
“…We used LSFG for assessment of ONH blood flow in the current study because its validity and reproducibility have been previously demonstrated [31,32] . In addition, our recent studies suggested that absolute MBR values for the ONH correlated with CBF, indicating the quantifiability of these values in the absence of large topographical and color differences in the ONH [31,33] .…”
Section: Discussionmentioning
confidence: 99%